Let f :
R
→
R
be a continuous function which satisfies
f
(
x
)
=
∫
0
x
f
(
t
)
dt
.
Then the value of
f
(
ln
5
)
is
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
But according to my solution, f ( x ) = ϕ , so, what's flaw in my solution @Calvin Lin sir
Log in to reply
Your answer is correct, but not the solution... you are dividing by 0 and taking the ln of 0 along the way.
The flaw in your solution is that you divided by 0.
f ( x ) = ∫ 0 x f ( t ) dt . . 1 Applying Newton's Leibniz rule
⇒
f
′
(
x
)
=
f
(
x
)
⇒
f
(
x
)
f
′
(
x
)
=
1
Integration both sides with respect to
dx
⇒
∫
f
(
x
)
f
′
(
x
)
dx
=
∫
dx
⇒
ln
∣
f
(
x
)
∣
=
x
+
c
⇒
f
(
x
)
=
k
e
x
.
.
2
Substituting value of
2
in equation
1
,
⇒
e
x
=
∫
0
x
k
e
t
dt
Again applying Newton's leibniz rule,
⇒
k
e
x
=
k
(
e
x
−
1
)
⇒
k
=
0
∴
f
(
x
)
=
0
⇒
f
(
ln
5
)
=
0
Note that when we divide by a variable, we only have 1 sided implication. In particular, we have to be very careful that we do not end up dividing by 0. If we do so, the conclusions are no longer valid.
Early on you divide by f ( x ) , later you take ln ∣ f ( x ) ∣ , but then you show that f ( x ) = 0 , meaning that you should not have performed those two operations (division and taking ln ) in the first place ;)
Log in to reply
Great observation...thanks...then what's the correct solution?
Have you solved with some other method?
Problem Loading...
Note Loading...
Set Loading...
Evaluating the given equation at x = 0 , we find that f ( 0 ) = 0 .
The second fundamental theorem gives f ′ ( x ) = f ( x ) , or f ′ ( x ) − f ( x ) = 0 . Multiplying with the integrating factor e − x , we can conclude that 0 = f ′ ( x ) e − x − f ( x ) e − x = d x d ( f ( x ) e − x ) = 0 . Thus f ( x ) e − x = k for some constant k . Now k = 0 since f ( 0 ) = 0 , so that f ( x ) = 0 for all x . In particular, f ( ln 5 ) = 0